2020
DOI: 10.3233/jad-191117
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations and Mortality of Individuals with Dementia: Evidence from Czech National Registers

Abstract: Background: Facing an increasing prevalence of dementia, the Czech Republic is developing a new nationwide strategy for the management and prevention of dementia. Lack of evidence about characteristics of individuals with dementia in the country is a major obstacle. Objective: The study aimed to 1) characterize individuals with dementia, 2) compare their mortality with the general population, and 3) analyze differences in survival between different dementia disorders. Methods: The study capitalizes on two nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…The shortest survival seen in VaD might be explained by the higher risk of stroke and other cardiovascular diseases, the late complications of cerebral infarctions and by the finding that demented patients receive poorer quality of care with worse outcomes after stroke 31 . These observations are supported by the findings of Broulikova et al 32 from Czech registers on hospitalized dementia patients.…”
Section: Discussionsupporting
confidence: 86%
“…The shortest survival seen in VaD might be explained by the higher risk of stroke and other cardiovascular diseases, the late complications of cerebral infarctions and by the finding that demented patients receive poorer quality of care with worse outcomes after stroke 31 . These observations are supported by the findings of Broulikova et al 32 from Czech registers on hospitalized dementia patients.…”
Section: Discussionsupporting
confidence: 86%
“…Third, the progression of white matter changes [ 50 ] and subcortical infarcts [ 51 ] may disrupt the integrity of neural networks including long-descending motor fibres and frontal–subcortical circuits that control motor and cognitive function, leading to falls [ 52 ]. Finally, the decrease in fall incidence after dementia diagnosis might be partially driven by an increase in hospitalization and death among people with dementia [ 53 , 54 ]. Moreover, people diagnosed with dementia often receive a variety of health care and home care services, such as personal care, house cleaning, laundry and accompanying walks, which may be beneficial in reducing the incidence of falls [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several nationwide studies have documented their databases on dementia registration. [19][20][21] Although each study is slightly different in the ICD-10 codes for dementia and features for de ning dementia, such as medications to treat dementia, underlying or contributing causes of death, and hospital admissions, our de nition is similar to previous studies. [19][20][21][22][23] Our results demonstrated that vestibular loss increased the risk of dementia and these results were correlated with the previous studies.…”
Section: Discussionmentioning
confidence: 97%